2009
DOI: 10.1038/ajh.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Arterial and Renal Nitric Oxide Bioavailability in Hypertensive Rats With Diabetes: Effect of  -Blockers

Abstract: Vascular and renal NO was significantly reduced in diabetic hypertensive rats and correlated with metabolic changes. Nebivolol reversed these effects in a manner consistent with enhanced endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Our observation that nebivolol treatment improved insulin sensitivity in transgenic RAAS mediated insulin resistant rats complement prior observations in Ang II treated [23] and overweight rodents [20], as well as insulin resistant hypertensive persons [8,18,19,25,26]. Indeed, previous studies have demonstrated that nebivolol reduces oxidative stress and increases tissue bioavailable NO levels in cardiovascular and renal tissue [7,17,23,27]. Reduced tissue bioavailable NO levels appears to be an important factor involved in Ang II-mediated elevation of blood pressure and decreased delivery of insulin and uptake of glucose by the skeletal muscle, processes critical for skeletal muscle utilization of glucose [1,6,14,15,16,28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our observation that nebivolol treatment improved insulin sensitivity in transgenic RAAS mediated insulin resistant rats complement prior observations in Ang II treated [23] and overweight rodents [20], as well as insulin resistant hypertensive persons [8,18,19,25,26]. Indeed, previous studies have demonstrated that nebivolol reduces oxidative stress and increases tissue bioavailable NO levels in cardiovascular and renal tissue [7,17,23,27]. Reduced tissue bioavailable NO levels appears to be an important factor involved in Ang II-mediated elevation of blood pressure and decreased delivery of insulin and uptake of glucose by the skeletal muscle, processes critical for skeletal muscle utilization of glucose [1,6,14,15,16,28].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, classic beta adrenergic receptor blockers have been shown to aggravate insulin resistance in hypertensive individuals [4, 17]. In the context of treatment of hypertension in insulin resistant individuals, nebivolol a selective β 1 -adrenergic blocker with vasodilatory and anti-oxidant properties, has been shown to improve oxidant stress and systemic insulin sensitivity; likely through reductions in NADPH oxidase activity and enhancement of endothelial NO synthase activity [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies found that, compared with normotensive rats, spontaneously hypertensive rats had lower NO bioavailability despite increased levels of eNOS [23]. The effects were even more pronounced after induction of diabetes among the hypertensive animals [21•]. The results were consistent with studies in rats that developed hypertension after aortic banding [24].…”
Section: Endothelial Dysfunction and The Role Of Nosupporting
confidence: 65%
“…Furthermore, ONOO – molecules themselves are highly reactive and oxidize lipids, cause cellular injury, and enhanced arterial contraction (Fig. 1) [21•].…”
Section: Endothelial Dysfunction and The Role Of Nomentioning
confidence: 99%
“…In a number of independent studies, nebivolol-induced NO release has also been linked to β 3 -receptor interactions as well as ATP-dependent, P2Y-mediated eNOS activation [17-20]. Nebivolol has also been reported to reverse eNOS uncoupling and interfere with oxidative stress processes, by reducing NADPH oxidase activity or by directly scavenging oxygen-derived free radicals [13,20-23]. …”
Section: Introductionmentioning
confidence: 99%